MARINE COLLAGEN: FROM EXTRACTION TO APPLICATIONS - Zena Sideek Tawffiq; Inas Hazim Ahmed; Samara Sameer Younis (International Journal of Pharmacy & Integrated Health Sciences, 2025)
Background: Numerous bioactive compounds discovered in aquatic life are used in the cosmetic and pharmaceutical fields. Numerous investigations have been conducted on the potential applications of collagen derived from these species in scientific research. The primary protein of connective tissue, collagen, is derived from a range of organisms. Due to the transmission of spongiform encephalopathy and bovine spongiform encephalopathy, the use of cattle as the primary source of collagen has been re-examined, while collagen derived from pigs is being increasingly rejected for religious reasons. The collection of collagen from marine sources is one substitute. Alternative sources of collagen include jellyfish, sponges, octopuses, squids, cuttlefish, and fish offal, which include bones, skin, scales, and fins. Objectives: The present review article provides a concise overview of collagen, including its properties, marine resources, approaches to extraction, peptides derived from collagen, Biological roles, and applications across multiple domains. Methodology: A variety of scientific sites, including PubMed, Science Direct, and Google Scholar, were searched electronically to gather the data. Results:  The versatility of marine collagen in repairing skin damage and delaying the ageing process, as well as its potential biotherapeutic uses in bone and wound rehabilitation and cosmetic products, makes it superior to terrestrial sources in many ways. It can also serve as a strategic avenue for technological advancement. Conclusion: The significant interest in marine collagenous materials is evident from their wide range of applications in nutrition, cosmetics, and healthcare.